Scientific assessment of theories of the origin of life and inclusion of the biblical model as an alternative explanation - Álvarez García, Andrés (2017)
The purposeof this research is to succinctly evaluate the main theories of the origin of life and to propose specific reasons to consider the biblical story as a reliable alternative to the origins. The research has a qualitative approach of descriptive character. For the data colletionis used the technique of bibliographic transfer, which allows to organize the state of the art of theories of the origin of life and the Genesis account. Severalauthors and research lines to list characteristics that are related to the appearance of life, but there is no clear definition of life in the scientific community. Theories of the world of RNA, panspermia, and prebiological membranes address the origin of life from an abiogenic, gradualist and evolutionary approach. On the other hand, in the protology of the Near East lies the account of Biblical Genesis as a historical, sequential and amictic narrative, which has differentiating characteristics with respect to the synchronic cosmogonies of Enuma Elish, Eridu Genesis and Atrahasis. In conclusion, the current theories of the origin of life carry significant limitations in their approach, which dissuades the possibility of considering the biblical text of creation as an alternative theory to the origin of life.